Metode Penyuluh Agama Islam Dalam Menanamkan Toleransi Antar Umat Beragama di Kelurahan Tanjung Langkat Kecamatan Salapian - Indah Putri Sari; Muaz Tanjung (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Basically, Islamic religious instructors have a very important role in society and empower themselves as Islamic religious instructors to show successful they are in counselling and guidance to community. Religious instructors are also the leading sector of Islamic community guidance, which has duties or obligations that are quite heavy, broad and the problem they face are even more complex. Islamic religious instructors are certainly not alone in carrying out quite heavy mandates, they must act as motivators, facilitators and, catalysts for Islamic da’wah in public. Indonesia, as a vast nation, encompasses a diverse range of religious beliefs, such as Islam, Christianity, Hinduism, Buddhism, and various other faiths. Consequently, fostering interreligious tolerance becomes imperative in ensuring social stability and safeguarding society from ideological pressures. Differences in religious beliefs is also a motivating factor not to bring each other down, to belittle one another each other tolerance is an attitude of mutual respect related to inter- religious relations and also freedom of and worship in society. One of the benefits of tolerance is that it makes it easier to realize unity and unity in the face of existing differences so that life will be comfortable and peaceful even in the midst of differences. Keywords: Method, Extension, Tolerance, People